Novel Arithmetic Equations for Mass Energy Equivalence, Newton’s Rings Radius, Wavelength and Speed of Light, Fine Structure Constant and Ideal Gas Law Correlated with eπ Based on Sayed’s Theorem - El-Mongy, Sayed A. (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Many proved scientific facts are mentioned in the generous Quran. This article introduces revisiting, revising and rewriting of well-established equations and laws of different applied fields of science and engineering. The eπ has been correlated with the mass energy equation of special relativity, fine structure constant, Newton`s rings radius, light wavelength, speed of light and ideal gas law. The correlated formulas were achieved based on the published Sayed`s equations and theorem. The fine structure constant was calculated and compared with a published value with 8.6435x10-5 discrepancy percentage. The novel deduced equations/formulas can be considered as confident mathematical expressions to be parallel used in the abovementioned and other scientific fields.